2020
DOI: 10.1186/s12864-020-07095-8
|View full text |Cite
|
Sign up to set email alerts
|

Selection signatures of Fuzhong Buffalo based on whole-genome sequences

Abstract: Background Fuzhong buffalo, a native breed of Guangxi Zhuang Autonomous Region, is traditionally used as a draft animal to provide farm power in the rice cultivation. In addition, the Fuzhong buffalo also prepared for the bullfighting festival organized by the locals. The detection of the selective signatures in its genome can help in elucidating the selection mechanisms in its stamina and muscle development of a draft animal. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Among them, 127 genes were overlapped which were considered to be candidate genes ( Supplementary Table S6 ). The annotations of candidate genes revealed the functions that may be associated with economic traits, including reproduction ( KHDRBS2 , GOLGA4 , BBX , BANF2 , INSL6 ) ( Cai et al, 2017 ; Guo et al, 2018 ; Ortega et al, 2016 ; Pini et al, 2020 ; Wang et al, 2016 ), growth ( RALGAPA1 , NCK1 , VGLL2, FGFR3 ) ( Aryal et al, 2015 ; Honda et al, 2017 ; Sun et al, 2020 ; Wen et al, 2016 ), meat quality ( PLIN4 ) ( Pena et al, 2019 ), and somatotype ( SYN3 ) ( An et al, 2019 ). We also obtained genes ( ELANE, AZU1 ) ( Cui et al, 2021 ; Zhang et al, 2021 ) related to immune response, which may result from long-term natural selection.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 127 genes were overlapped which were considered to be candidate genes ( Supplementary Table S6 ). The annotations of candidate genes revealed the functions that may be associated with economic traits, including reproduction ( KHDRBS2 , GOLGA4 , BBX , BANF2 , INSL6 ) ( Cai et al, 2017 ; Guo et al, 2018 ; Ortega et al, 2016 ; Pini et al, 2020 ; Wang et al, 2016 ), growth ( RALGAPA1 , NCK1 , VGLL2, FGFR3 ) ( Aryal et al, 2015 ; Honda et al, 2017 ; Sun et al, 2020 ; Wen et al, 2016 ), meat quality ( PLIN4 ) ( Pena et al, 2019 ), and somatotype ( SYN3 ) ( An et al, 2019 ). We also obtained genes ( ELANE, AZU1 ) ( Cui et al, 2021 ; Zhang et al, 2021 ) related to immune response, which may result from long-term natural selection.…”
Section: Resultsmentioning
confidence: 99%
“…The overlap of the top 1% windows in each method was considered as candidate signatures of selection. Genomic regions identified by at least two methods were considered to be candidate regions of positive selection (Sun et al, 2020). In addition, π and Fst were computed with 5 kb sliding window and 2 kb step by using VCFtools for each candidate gene.…”
Section: Selective Sweep Identificationmentioning
confidence: 99%
“…(2016) suggested that ARHGAP6 is indispensable in the growth and development of porcine. RALGAPA1 is linked to reproductive traits, hatching rate, and egg production in chickens (Sun et al., 2020). CCL19 is involved in the release of sequestered calcium ions into the cytosol.…”
Section: Discussionmentioning
confidence: 99%